2018
DOI: 10.12816/0044631
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism among Saudi Medical Students

Abstract: Background: Student absenteeism refers to the frequent absence from classes without any good reason and thought to be the primary concern in health profession education worldwide mainly in medical school. Methods and Material: This study is a cross sectional design conducted in 152 medical students of King Saud Bin Abdulaziz University for Health Sciences (KSAU-HS), Saudi Arabia. A self-reported questionnaire was used to determine absenteeism behavior, contributing factors of absenteeism, and level of satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In the previous study conducted on first-year medical students, exhibits that self-efficacy made an absolute involvement to the academic achievement and that voluntary participation in learning modules mediated a positive association between motivation and learning policies 4. Mostly, studies on student success reportsthat class attendance is a reliable predictor associated with better outcomes in terms of improving cumulative grade point average of the students who do best 5,6…”
Section: Introductionmentioning
confidence: 96%
“…In the previous study conducted on first-year medical students, exhibits that self-efficacy made an absolute involvement to the academic achievement and that voluntary participation in learning modules mediated a positive association between motivation and learning policies 4. Mostly, studies on student success reportsthat class attendance is a reliable predictor associated with better outcomes in terms of improving cumulative grade point average of the students who do best 5,6…”
Section: Introductionmentioning
confidence: 96%
“…[ 17 18 19 ] Class attendance is a reliable predictor associated with better outcomes in terms of improving cumulative grade point average of the students who do best. [ 20 21 22 ] Attendance is more important for enhancing grades. Attending clinical and tutorial-based class events have a positive correlation with overall examination score.…”
Section: Introductionmentioning
confidence: 99%
“…Qutub and colleagues’ study on absenteeism among Saudi medical students found that absenteeism impacted academic performance negatively. The study concluded that academic performance can be improved when students change their perspective toward attendance [ 17 ]. Another study on the effect of absenteeism on the academic performance of Saudi medical students surveyed 300 students using a cross-sectional questionnaire on 300 students [ 18 ].…”
Section: Introductionmentioning
confidence: 99%